(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background: Varied results emerging out of various studies have created a controversy about effect of intravenous fluid supplementation on duration of phototherapy required in term babies with severe hyperbilirubinemia. Paucity of literature warrants this study. Objective: The objective of this study is to evaluate the probable effect, if any, of intravenous fluid supplementation in decreasing the duration of phototherapy requirement in healthy term babies with hyperbilirubinemia. Methods: In this prospective study healthy term neonates (37-41 week gestation) from day 1 up to 28 days of life with serum bilirubin (>18 mg/dl and <25 mg/dl) for treatment with phototherapy were randomly allocated to two groups, study group received intravenous fluid for total 16 hours along with breast feed and control group given only breast feeds. Results: Baseline variables like sex distribution, age at admission, gestation, birth weight, admission weight, appropriate for gestational age, mode of delivery, oxytocin use, breast feeding and serum bilirubin level at the time of inclusion in study, were comparable in both control and study group. Required duration of Phototherapy was 59.03 + 11.79 hrs in control group and in study group 32.43 + 23.12 hrs (P <0.001). Duration of phototherapy was significantly less in study group than control group (P < 0.001). It was 27 hours shorter in extra fluid group. Conclusions:Based on our findings it can be concluded that required duration of phototherapy significantly decreases with the use of extra fluid supplementation in neonates with hyperbilirubinemia